Effect of aspirin use on conversion risk from mild cognitive impairment to Alzheimer’s disease - Choi, Bo Kyu; Jin, Yeonju; Lee, Hokyung; Kim, Sung-Woo; Park, Sojeong; Hong, Ickpyo; Baek, Min Seok (Frontiers in Aging Neuroscience, 2025)
BackgroundThe potential effect of the antiplatelet and anti-inflammatory properties of aspirin on Alzheimer’s disease development, especially its role in the progression from mild cognitive impairment to Alzheimer’s disease dementia, remains controversial. To evaluate the association between aspirin, use and the risk of conversion to Alzheimer’s disease dementia among individuals diagnosed with mild cognitive impairment.MethodsIn this retrospective population-based cohort study, we used the Korean National Health Insurance Service database to collect data on patients with mild cognitive impairment enrolled between 2013 and 2016 and followed up until 2021. In total, 508,107 patients initially diagnosed with mild cognitive impairment (192,538 with aspirin prescriptions and 315,569 without aspirin prescriptions) were enrolled. Aspirin use was assessed by extracting information from the Korean National Health Insurance Service database using aspirin prescription codes. The primary outcome was newly diagnosed Alzheimer’s disease dementia. Hazard ratios and 95% confidence intervals for Alzheimer’s disease were analyzed according to aspirin use using Cox proportional hazards regression analysis. Secondary outcomes included ischemic and hemorrhagic stroke risk associated with aspirin use.ResultsThe data of 508,107 individuals were analyzed (mean [standard deviation] age, 67.6 [10.7] years; 66.8% women and 33.2% men), and 39,318 developed Alzheimer’s disease (22,572 controls and 16,746 using aspirin). The rate of conversion to Alzheimer’s disease was lower in the aspirin user group, and the time to Alzheimer’s disease dementia occurrence was longer than in the nonuser group. A decreased Alzheimer’s disease dementia risk was found in patients using aspirin in Model 2 (adjusted hazard ratio, 0.939; 95% confidence interval, 0.920–0.959), with more pronounced effects in individuals aged ≥65 years (Model 2 adjusted hazard ratio, 0.934; 95% confidence interval, 0.914–0.955). For hemorrhagic stroke, the risk increased with aspirin use across all age groups, with the highest risk observed in younger patients (Model 2 adjusted hazard ratio, 5.082; 95% confidence interval, 4.838–5.338).ConclusionAspirin use was associated with reduced Alzheimer’s disease risk in older patients with mild cognitive impairment. Notably, the bleeding risk associated with aspirin use should be considered, and personalized treatment should be provided.